Prognostic Impact of PHIP Copy Number in Melanoma: Linkage to Ulceration - Bezrookove, Vladimir (2013)
Ulceration is an important prognostic factor in melanoma whose biologic basis is poorly understood. Here we assessed the prognostic impact of pleckstrin homology domain-interacting protein (PHIP) copy number and its relationship to ulceration. PHIP copy number was determined using fluorescence in situ hybridization (FISH) in a tissue microarray cohort of 238 melanomas. Elevated PHIP copy number was associated with significantly reduced DMFS (P = 0.01) and DSS (P = 0.009) by Kaplan-Meier analyses. PHIP FISH scores were independently predictive of DMFS (P = 0.03) and DSS (P = 0.03). Increased PHIP copy number was an independent predictor of ulceration status (P = 0.04). The combined impact of increased PHIP copy number and tumor vascularity on ulceration status was highly significant (P< 0.0001). Stable suppression of PHIP in human melanoma cells resulted in significantly reduced glycolytic activity in vitro, with lower expression of LDH5, HIF1A, and VEGF, and was accompanied by reduced microvessel density in vivo. These results provide further support for PHIP as a molecular prognostic marker of melanoma, and reveal a significant linkage between PHIP levels and ulceration. Moreover, they suggest that ulceration may be driven by increased glycolysis and angiogenesis.